A Prospective Study Comparing Treatment Outcomes Of Empyema Management Techniques: Chest Tube Vs. Video-Assisted Thoracoscopic Surgery - Rashnoo, Fariborz; Farsad, Seyed Mehdi; Pejhan, Saviz; Faz, Atena Alipour; Mirhashemi, Seyed Hadi; Soori, Mohsen; Oshidari, Bahador; Nasrollah, Esmaeil Haji; Hakakzadeh, Azadeh; Peyvandi, Hassan (Russian open medical journal, 2022)
Introduction — High mortality and morbidity rate of empyema, despite effective antibiotic therapy, highlights the need to determine the optimal drainage method as a first-line surgical intervention. Controversies behind the treatment choice for empyema encouraged us to conduct this study aimed at demonstrating efficacy and differences of two techniques of clinical approach to empyema, chest tube and video-assisted thoracoscopic surgery (VATS) with respect to outcomes. Material and Methods — We recruited 60 eligible patients with empyema and distributed them among two groups according to applied treatment strategies, either chest tube treatment method (Group I, 30 subjects) or VATS (Group II, 30 patients). Data were statistically analyzed by SPSS software, version 19. Then, the one-sample Kolmogorov–Smirnov test confirmed the normality of data distribution, and independent samples t-test was performed. Statistical significance was assumed at p<0.05. Results — We established that the length of hospital stay (p=0.002), the need for second intervention (p<0.001), and rate of recurrence (readmission) (p=0.001) were significantly lower in patients treated with VATS, compared with patients who were subjected to chest tube drainage. Additionally, patients who underwent VATS exhibited higher satisfaction level (p=0.03) and improved clinical condition at the time of discharge (discharged without chest tube) (p<0.001), than those from Group I. Radiographic examination on postoperative day 7 revealed a higher rate of complete cure (normal lung expansion) in the VATS group (p=0.004). Conclusion — According to the results of our study, VATS is a better treatment technique of empyema, compared with chest tube.